Mental Health Behind Japan’s Economic and Social Productivity - Prameswari, Anisa Indira; Darmastuti, Shanti; Fathun, Laode Muhamad (Sospol : Jurnal Sosial Politik, 2019)
This article describes the impacts given by depression as mental health disorder and suicidal behavior towards Japan?s economy and social productivity. Depression and suicide have become one of the main causes of mortality among other health conditions in Japan. Both depression and suicidal behavior are non-communicable, yet both can influence psychological states of other people near the patient. Depression and suicidal behavior are challenging for countries with high mortality caused by suicide, especially towards those who also have ageing population like Japan. Hence, this article will analyze further costs faced by Japan along with reviewing policies taken to overcome their mental health challenges. This study uses qualitative descriptive design with case study method. This study also uses secondary analysis to answer mentioned challenges. Result shows that Japan faces economic loss to sustain their mental health expenses and psychological expenses for the family left by the victims of depression and suicide, as suicide trend is popular among adults and youths in Japan. Depression and suicidal behavior can also affect individual?s productivity. The authors expect that this can be used to give broader knowledge on non-traditional contemporary global issues.